Método Montessori en la lectoescritura con estudiantes de segundo grado de la Escuela de Educación Básica Particular “Sendero”, Loja 2023 - Yaguana Ordóñez, Yajaira Fernanda (2023)
This study focuses on the Montessori Method, a pedagogy recognized for its individualized and respectful approach to child development. The main objective is to establish the relationship between the Montessori method and the strengthening of literacy through a didactic guide for second grade students, where, through research, we will seek to identify the levels of literacy presented by the students and from there generate a set of strategies to improve reading and writing skills. The research is quantitative and descriptive in nature, since it seeks to describe the application of the Montessori method to strengthen literacy in second grade students. To achieve this, standardized tests were applied to evaluate the level of literacy before and after the intervention, and questionnaires were also administered to teachers and students. The results of the study revealed that the application of the Montessori Method significantly contributes to the strengthening of reading and writing skills, as well as demonstrating greater autonomy and motivation, and teachers highlighted a positive perception of the Montessori Method and recognized its ability to promote the integral development of children. Finally, the study shows that the application of the Montessori Method is highly beneficial for the strengthening of literacy in second graders, since the individualized and respectful approach to each child's development promotes an environment conducive for learning and stimulates the acquisition of skills in a more meaningful way. The results suggest that the Montessori Method can be an effective and enriching alternative in the context of teaching literacy. Key words: Montessori method, literacy, teaching-learning,